2021
DOI: 10.3390/jcm10091953
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk and Phenotype Correlation of Primary Open-Angle Glaucoma Based on Rho-Kinase Gene Polymorphisms

Abstract: Rho-associated coiled-coil kinase (ROCK) signaling can affect glaucoma risk by regulating trabecular meshwork outflow. We investigated the effect of ROCK gene polymorphism on the risks of primary open-angle glaucoma (POAG) and POAG-related phenotypes including intraocular pressure (IOP) in a Korean population. A total of 24 single-nucleotide polymorphisms (SNPs) from ROCK1 and ROCK2 were selected and genotyped for 363 POAG patients and 213 healthy controls. Among the 363 POAG patients, 282 were normal-tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The ROCK1 gene rs35996865 polymorphism mapping to the 5ʹ-UTR has been reported to be significantly associated with colorectal cancer 18,19 , obesity-related metabolic syndrome 20 , renal cell carcinoma 21 , respiratory distress syndrome 22 , nonsyndromic cleft palate 17 , and systemic sclerosis 23 , but not with Behçet's disease 24 or Alzheimer's disease 25 . Although no association of this polymorphism was noted with primary open-angle glaucoma in a Turkish population 26 , this variant is nominally associated with risk of high-tension glaucoma in a Korean population 27 .…”
Section: Discussionmentioning
confidence: 76%
“…The ROCK1 gene rs35996865 polymorphism mapping to the 5ʹ-UTR has been reported to be significantly associated with colorectal cancer 18,19 , obesity-related metabolic syndrome 20 , renal cell carcinoma 21 , respiratory distress syndrome 22 , nonsyndromic cleft palate 17 , and systemic sclerosis 23 , but not with Behçet's disease 24 or Alzheimer's disease 25 . Although no association of this polymorphism was noted with primary open-angle glaucoma in a Turkish population 26 , this variant is nominally associated with risk of high-tension glaucoma in a Korean population 27 .…”
Section: Discussionmentioning
confidence: 76%
“…ROCK1 is expressed in the TM as demonstrated by a study using TM tissue derived from monkeys [196]. A study with 363 POAG patients and 213 healthy controls in Korea showed that the SNPs rs288979, rs1006881, rs35996865, rs10083915 and rs11873284 in ROCK1 are associated with an increased risk of HTG but not with NTG [108]. The ROCK1 polymorphism rs35996865 was found to have no association with POAG in a Turkish patient population [197].…”
Section: Rock1mentioning
confidence: 99%
“…The qualified studies were published between November 2001 and January 2024. Among these studies, 55 were case control studies conducted in 11 countries and regions: 10 in China [22,26,37,40,53,54,57,66,69,70], 13 in Korea [20,25,30,39,47,[58][59][60][62][63][64]67,71], 18 in Japan [18,19,23,24,27,[31][32][33][34]38,41,42,46,48,49,51,52,56], 3 in Poland [55,61,65], 2 in the U.S [36,50], 3 in England [16,17,45], 2 in Australia [21,…”
Section: Characteristics Of Qualified Studiesmentioning
confidence: 99%